"I've Fallen and I Can't Get Up, " a Basic Primer for Caregivers to Understand Falls in Persons With Dementia, Alzheimer's Disease, and Cognitive Impairment. (August 2015) - Rowe, Jimmy
This article seeks to demystify the complexity of what constitutes dementia, Alzheimer's disease, and cognitive impairment as it relates to identifying the basic contexts of these diseases in relationship with falls and fall prevention. It further will identify the new changes in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) that replaces the term dementia and provides the new diagnostic framework for major and mild neurocognitive functioning. This article additionally provides some practical strategies for caregivers to equip themselves to understand some of the difficulties and challenges that they face when dealing with loved ones or patients who become afflicted by these diseases.